PERANCANGAN WEB BASED LEARNING SEBAGAI MEDIA PEMBELAJARAN BERBASIS ICT - Firmansyah, Ricky; Saidah, Iis (Jurnal Informatika, 2016)
ABSTRACT The media is very important component of communication process. The effectiveness of media is very influential on extent to which a communication role will be accepted by the audience with fast and precise, or vice versa. E-Learning is present as ICT based learning media that allows students and teachers interact in different places. Web Based Learning (WBL) is used as one part of the E-Learning. This study focuses on designing web-based ICT as a learning medium that is used for students and teacher interaction media that equipped with learning material in content form that will be delivered. Students can learn about learning materials that submitted by teachers through the website anytime and anywhere as long as internet access is available, including taking a test in accordance with the time specified by the teacher. Waterfall method is used as a system development method implemented using the server-side web programming scripting like PHP MySQL. After using the system, questionnaire survey conducted on students and teachers. The results from this study is 71% of the number of students who complete the survey claimed that the system is easy and fun to use and 68% of the number of teachers who complete the survey claimed that this system is very assist with their work, especially in managing test scores. Keywords: design, e-learni